Analysis of the disparity between recurring and temporary collaborative performance: A literature review between 1994 and 2021 - Sara Rye (Logistics, 2022)
Background: Performance frameworks are common ways to guarantee the success of a collaboration by assessment/improvement of the organisations. However, collaborative performance in recurring collaborations (RC) and temporary ones (TC) are being measured differently due to their inherent characteristics; Methods: A systematic review of 282 existing studies, from 2000 onwards, into collaborative networks divided between RC and TC based on the duration of collaboration and the application of the studies was performed. The result gave rise to the thematic analysis of the textual narratives, as well as a quantitative meta-summary of the synthesis; Results: The review shows two different approaches to guarantee the performance of the collaboration. The first group provide a recipe for success by recognizing the causal relationship between nine collaborative measures, including information and risk sharing, trust, commitment, agility, power balance, leadership, prior-experience, and alignment. The second group ensures the success of collaboration by selecting suitable partners based on their previous performance emerging through synergy, readiness, agility and internal-external factors; Conclusions: The reasoning behind these differences are discussed and the current gaps in research are outlined.
Keywords: 650; collaboration; collaborative performance; inter-organisational collaboration; partner selection; recurring collaboration; supply chain; temporary collaboration; virtual organisation